“Poda en el Cultivo de Cacao (Theobroma Cacao) en la Finca María Isabel, ubicada en el Recinto San Antonio del Cantón Catarama” - Márquez Moretta, Ariana Valeria (2019)
SUMMARY Within the clone varieties existing on the farm, there are two hectares mixed of the following clones: "EET-95", "EET-103", "EET-19", these clones are sensitive to solar radiation, for reasons of adaptability this clone is considered self-compatible "EET-96", as difficult rooting. In the Maria Isabel farm, due to problems of knowledge of parts of the farmers, has caused an aggressive pruning, causing a low productivity of 50%, which would be 10 quintals per year, causing an aging of the branches due to solar radiation attack, damaging the floral bearings. In the Maria Isabel farm, it has been characterized that they carry out two types of pruning, the one of formation, and the pruning of maintenance, in spite of this there was carelessness, in certain lots one finds plantations without pruning because of problem with the lunar phases, because have enough personnel, however the phytosanitary pruning have knowledge but do not do it with constancy for that reason was found plantation without the realization, therefore the neglect brings diseases, and the lack of decontamination of tools too, that's why within the plantation machete disease was found.-It is recommended to perform the four types of pruning taking into account the age of the crop, with the time of year, without neglecting the lunar phases. Keyword: Pruning, cocoa, and Maria Isabel farm